The Real Earnings Management and Tax Aggressiveness in Indonesia - Hajawiyah, Ain; Perdana, Anugrah Rinata; Wahyuningrum, Indah Fajarini Sri (Accounting Analysis Journal, 2023)
Purpose: This research aimed to examine the effect of real earnings management on tax aggressiveness. Method: The study used a quantitative approach using secondary data from the manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021. The sampling technique used is the purposive sampling method and the analysis technique used is multiple linear regression using SPSS 25 software. Findings: The findings of this study indicate that real earnings management significantly negatively affected tax aggressiveness. Variable control profitability significantly positively affected tax aggressiveness. Whereas variable control leverage does not affect tax aggressiveness. Moreover, variable size significantly positively affected tax aggressiveness. Novelty: The study uses real earnings management as an independent variable instead of accrual earnings management, which has been commonly used in previous studies. Real earnings management is considered effective in a company’s earnings management strategy because it manipulates data related to day-to-day operation activity of the company. Keywords: Real Earnings Management; Tax Aggressiveness; Profitability; Leverage; Firm Size